Polish Independent Press Review, no. 6 (1989) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). Cultural and Political Aspects of Women's Problems in Poland / by Anna PomianMost of the problems that women encounter in Poland should be viewed against the political and cultural background that determines much of their activity. Women and Their Social Roles / by Anna PomianThe results of a survey conducted among working women revealed the inherent conflict they experienced in trying to reconcile the demands of full-time employment with those of bringing up a family in Poland's difficult economic conditions. How Polish Women View Their Work / by Anna PomianA further study in the independent report on Polish women provided several insights and first-hand documentation on how women viewed their work and drew attention to a number of disturbing features of the work place. Women's Health Problems: External and Personal Factors / by Anna PomianAdverse working conditions and a generally low standard of living undoubtedly contribute to the poor level of health among women in Poland, but there is also evidence that women neglect areas of health for which they alone are responsible. "Amazonka": An Underground Publication for Women / by Anna PomianOnly one publication for women has appeared in Poland's underground circulation. Political Activism and Its Consequences for Polish Women / by Anna PomianThis paper looks at some of the ways in which Polish women have engaged in political activity since the birth of Solidarity nine years ago in August 1980, and the varied success that they have achieved.